Exploring the Trace of God's Presence in Daily Life Between Faith and Reason - Indriati Tjipto Purnomo; Pujiwati Pujiwati (International Perspectives in Christian Education and Philosophy, 2024)
Reason and faith must be balanced in order to develop a relationship with God. Both complement one another, despite the fact that they are frequently seen as mutually exclusive. Through the experience of faith, humans despite their limited intelligence are able to recognize the existence of God. This process involves more than just thinking; it also involves the light of faith, which makes it possible to sense God's presence in day-to-day existence. The secret to developing a close relationship with God is having a high-quality spiritual life. The development of a spiritual quality of life can be achieved through adoration, meditation, and prayer. This article's research methodology, which employs the library method, presents opinions from a range of sources that are pertinent to the growth of a relationship with God. In conclusion, a balance between reason and faith is necessary for the pursuit and discovery of God. People can sense God's presence in their lives through the quality of their spiritual lives, their theological viewpoint, and their experience of faith in Christ.